2020
DOI: 10.1055/s-0040-1713843
|View full text |Cite
|
Sign up to set email alerts
|

Acute Sensory and Autonomic Neuronopathy: A Devastating Disorder Affecting Sensory and Autonomic Ganglia

Abstract: Acute-onset and severe sensory and autonomic deficits with no motor dysfunction, typically preceded by a febrile illness, with poor recovery, and often fatal outcome are the hallmark features of acute sensory and autonomic neuronopathy (ASANN). Pathologically and electrophysiologically, ASANN is characterized by an extensive ganglionopathy affecting sensory and autonomic ganglia with preservation of motor neurons. Consequently, patients, usually children or young adult, develop acute-onset profound widespread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This clinical manifestation suggests that the pathophysiology of AASN might be the same as in that of Guillain-Barré syndrome (GBS). In GBS, post-infectious immune-mediated mechanisms cause the disruption of the blood-nerve barrier leading to demyelination or axonal loss [ 1 , 8 ]. Our MRI with contrast findings suggest that inflammation in the dorsal roots, together with the posterior column of the spinal cord and cervical dorsal root ganglia, is one of the causes of sensory disturbance in patients with AASN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This clinical manifestation suggests that the pathophysiology of AASN might be the same as in that of Guillain-Barré syndrome (GBS). In GBS, post-infectious immune-mediated mechanisms cause the disruption of the blood-nerve barrier leading to demyelination or axonal loss [ 1 , 8 ]. Our MRI with contrast findings suggest that inflammation in the dorsal roots, together with the posterior column of the spinal cord and cervical dorsal root ganglia, is one of the causes of sensory disturbance in patients with AASN.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, especially in the early stages of AASN, MRI with contrast facilitates the diagnosis of AASN. It is difficult for physicians to differentiate AASN from other mimicking disorders, such as sensory GBS, acute sensory ataxic neuropathy with antiganglioside antibodies, Sjögren disease or paraneoplastic neuronopathy because there are no specific biomarkers for AASN [ 1 , 8 ]. We considered sensory GBS or acute sensory ataxic neuropathy with antiganglioside antibodies but disregarded them because of the rarity of severe autonomic dysfunction in these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, mechanical allodynia—which is a common symptom when nerves receive prolonged exposure to inflammatory cytokines ( Jensen and Finnerup, 2014 ; Beaulieu-Laroche et al, 2020 ; Bonet et al, 2021 )—provoked by the VN-NDT had the best test accuracy in detecting digestion alterations and burning sensation in the stomach. Indeed, gastrointestinal dysfunctions are very common in acute and chronic APNs ( Freeman, 2005 ; Oaklander and Nolano, 2019 ; Gutierrez et al, 2020 ; Marathe et al, 2020 ). Since the perioperative and postsurgery risks of cardiovascular side events ( Lankhorst et al, 2015 ; Ho et al, 2020 ; Malaty et al, 2021 ) are higher in post-COVID-19 patients and patients with APN, which are difficult to be studied, it is possible to adopt the VN-NDT as a sensitive, faster, and riskless screening test.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report for the first time that a sequence of neck movements can systematically affect HR, both in males and females, suggesting a key role of the stretch on the neck portion of the VN in HR modulation. Gutierrez and coworkers reported that a patient with acute sensory and autonomic neuropathy had her symptoms relieved by neck movements ( Gutierrez et al, 2020 ) which are included in the VN-NDT. Therefore, we can argue that studying the VN-NDT effects can be helpful in diagnosis and symptoms management in autonomic dysfunctions.…”
Section: Discussionmentioning
confidence: 99%